P-583 PCOS patients got better IVF/ICSI outcomes with "higher" progesterone level on hCG day: a retrospective study of Ten years data. (30th June 2022) - Yang, S; Rong, L; Xiumei, Z; Lina, W; Haiyan, W; Caihong, M; Ping, L; Jie, Q
Abstract: Study question: We aimed to investigate whether serum Progesterone (P) on the day of hCG trigger can be used as a biomarker to predict the IVF/ICSI outcomes in PCOS patients. Summary answer: PCOS patients got better IVF/ICSI outcomes with "higher" progesterone level (2.7-5.9mmol/L). What is known already: There were several studies suggesting serum Progesterone (P) on the day of hCG trigger can be used as a biomarker to predict IVF outcomes, and to decide fresh cycle embryo transfer or frozen all. But there was few study focus on PCOS patients. Study design, size, duration: This is a single-center retrospective cohort study in PCOS women undergoing the first transfer of an IVF cycle between January 1 st 2010 and December 31 th 2019. There were 141, 539 oocyte retrieval cycles during the study period, and 97, 189 cycles were their first IVF cycle. PCOS was diagnosed according to the Rotterdam criteria. Among them, 3, 146 cycles full filled the inclusion and exclusion criteria, and all with two embryos transferred on Day 3. Participants/materials, setting, methods: We compared the live birth rate of fresh embryo transfer, stratified for serum P level. We looked for interaction between serum P level and live birth rate of fresh cycles. The serum P level within normal range (< 6nmol/L) on the day of hCG trigger day was divided into 4 quartiles. The four quartiles were defined as ≤ 1.35 nmol/L (Q1), >1.35-1.93 nmol/L (Q2), >1.93-2.7 nmol/L (Q3), >2.7 nmol/L (Q4). Main results and the role of chance: The baseline characteristics with no different between groups, except BMI. The patients in Q4 group with lowest BMI, significantly higher number of oocytes retrieved and live birth rate (P < 0.05) . The Logistic regression analysis of the relative factors on live birth rate including BMI, basal LH and number of oocytes retrieved [P = 0.003, 0.030, 0.037 respectively, 95%CI (1.022, 1.111), (1.004, 1.076), (1.002, 1.082)]. Limitations, reasons for caution: Due to the retrospective nature of this study, a well-designed and matched large sample prospective study is needed. The definition of elevated P level and the method of hormonal assessments were different between studies, this limiting the comprehensive analysis of researches and the further verification of existing results. Wider implications of the findings: PCOS patients who with normal range P level on hCG day, got better IVF/ICSI outcomes with "higher" progesterone level (2.7-5.9mmol/L). Weight control is important for PCOS patients accepting IVF treatment. Trial registration number: NOT APPLICABLE